European Organisation for Research and Treatment of Cancer consensus recommendations for the treatment of mycosis fungoides/Sézary syndrome – Update 2017. (May 2017) - Trautinger, Franz; Eder, Johanna; Assaf, Chalid; Bagot, Martine; Cozzio, Antonio; Dummer, Reinhard; Gniadecki, Robert; Klemke, Claus-Detlev; Ortiz-Romero, Pablo L.; Papadavid, Evangelia; Pimpinelli, Nicola; Quaglino, Pietro; et al.
Abstract: In order to provide a common standard for the treatment of mycosis fungoides (MF) and Sézary syndrome (SS), the European Organisation for Research and Treatment of Cancer–Cutaneous Lymphoma Task Force (EORTC-CLTF) published in 2006 its consensus recommendations for the stage-adapted selection of management options for these neoplasms. Since then, the understanding of the pathophysiology and epidemiology of MF/SS has advanced, the staging system has been revised, new outcome data have been published and novel treatment options have been introduced. The purpose of the present document is to update the original recommendations bearing in mind that there are still only a limited number of controlled studies to support treatment decisions for MF/SS and that often treatment is determined by institutional experience and availability. This consensus on treatment recommendations was established among the authors through a series of consecutive consultations in writing and a round of discussion. Recommended treatment options are presented according to disease stage, whenever possible categorised into first- and second-line options and supported with levels of evidence as devised by the Oxford Centre for Evidence-Based Medicine (OCEBM). Skin-directed therapies are still the most appropriate option for early-stage MF, and most patients can look forward to a normal life expectancy. For patients with advanced disease, prognosis is still grim, and only for a highly selected subset of patients, prolonged survival can be achieved with allogeneic stem cell transplantation (alloSCT). There is a high need for the development and investigation in controlled clinical trials of treatment options that are based on our increasing understanding of the molecular pathology of MF/SS. Highlights: Skin directed therapies are the preferred option for the management of early stage disease. For advanced stages with poor prognosis systemic therapies can provide effective palliation. With allogeneic stem cell transplantation prolonged survival can be achieved in selected patients. Novel immunotherapies have shown significant activity in cutaneous T-cell lymphomas.